Evaluation of ground-source heat pump combined latent heat storage system performance in greenhouse heating - Benli, Hueseyin; Durmus, Aydin (Elsevier Science Sa, 2009)
The use of renewable energy for greenhouse heating in winter and cold days, helps to save fossil fuels and conserve green farm environment on the one hand, and on the other hand, enhances the quality of agricultural products, reduces production costs and limits the release of greenhouse gases. In this study, a ground-source heat pump-phase change material (GSHP-PCM) latent heat storage system was developed to use natural energy, to the extent possible, for thermal environment control of the greenhouse. The coefficient of performance of the heat pump (COP(HP)), that of the overall system (COP(sys)) and the energy capacity of the PCM during the charge-discharge phases has been determined. Based upon the measurements made in the heating mode from 1 September 2005 till 30 April 2006 in Elazig, Turkey, the average heating COP(HP) of the GSHP unit and the overall system COP(sys) were obtained to be in the range of 2.3-3.8 and 2-3.5, respectively. These results showed that the utilization of a GSHP-PCM system is a suitable approach for greenhouse heating in this district. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Ground-source heat pump (GSHP); Horizontal heat exchanger (HHE); Latent heat storage (LHS); Phase change material (PCM); The coefficient of performance (COP); Greenhouse